2001
DOI: 10.1006/dbio.2001.0196
|View full text |Cite
|
Sign up to set email alerts
|

Inwardly Rectifying K+ Channels in Spermatogenic Cells: Functional Expression and Implication in Sperm Capacitation

Abstract: To fertilize, mammalian sperm must complete a maturational process called capacitation. It is thought that the membrane potential of sperm hyperpolarizes during capacitation, possibly due to the opening of K(+) channels, but electrophysiological evidence is lacking. In this report, using patch-clamp recordings obtained from isolated mouse spermatogenic cells we document the presence of a novel K(+)-selective inwardly rectifying current. Macroscopic current activated at membrane potentials below the equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 39 publications
5
114
0
Order By: Relevance
“…In living cells, membrane potential is defined by the gradients of K + , Na + and Cl − with potassium channels playing a crucial role in its regulation. Noncapacitated epididymal murine spermatozoa are slightly depolarized at about −40 mV, however they hyperpolarize up to −60 mV upon capacitation [137]. This effect is attributed to potassium permeability and two members of the Slo family of potassium channels have been recently proposed to play a role in this process [21,25,26,29,31,33,[138][139][140][141].…”
Section: Potassium Channels Of Spermmentioning
confidence: 99%
“…In living cells, membrane potential is defined by the gradients of K + , Na + and Cl − with potassium channels playing a crucial role in its regulation. Noncapacitated epididymal murine spermatozoa are slightly depolarized at about −40 mV, however they hyperpolarize up to −60 mV upon capacitation [137]. This effect is attributed to potassium permeability and two members of the Slo family of potassium channels have been recently proposed to play a role in this process [21,25,26,29,31,33,[138][139][140][141].…”
Section: Potassium Channels Of Spermmentioning
confidence: 99%
“…After in vitro capacitation in bicarbonate-containing media at pH 7.4, pH i increases Ͼ0.3 units (2,8,9). When intracellular alkalinization is prevented by glucose incubation, bovine sperm fail to capacitate (8, 10).Measurements with voltage-sensitive fluorescent dyes indicate that noncapacitated murine sperm are relatively depolarized (approximately Ϫ30 mV) and hyperpolarize to approximately Ϫ60 mV during capacitation (4,11,12). Indirect measurements attribute the capacitation-associated hyperpolarization to an increase in K ϩ permeability (4) and a block of epithelial sodium channels (ENaCs) (13).…”
mentioning
confidence: 99%
“…Measurements with voltage-sensitive fluorescent dyes indicate that noncapacitated murine sperm are relatively depolarized (approximately Ϫ30 mV) and hyperpolarize to approximately Ϫ60 mV during capacitation (4,11,12). Indirect measurements attribute the capacitation-associated hyperpolarization to an increase in K ϩ permeability (4) and a block of epithelial sodium channels (ENaCs) (13).…”
mentioning
confidence: 99%
“…Altogether the set of changes required for this maturation process is called capacitation and involves the development of a distinctive sperm motility pattern known as hyperactivation, and the sperm capacity to undergo the AR, an exocytotic event that allows the sperm to fertilize the egg. During sperm capacitation PKA is activated (Harrison 2004 ), leading to tyrosine phosphorylation increases (Visconti et al 1995a , b ); pH i (Zeng et al 1995 ) and [Ca 2+ ] i elevate (Baldi et al 1991 ;Breitbart 2003 ;DasGupta et al 1993 ;Suarez et al 1993 ;Xia and Ren 2009 ); plasma membrane composition and organization are modifi ed (Cross 1998 ;Davis 1981 ;Gadella and Harrison 2000 ;Go and Wolf 1983 ;Travis and Kopf 2002 ;Visconti et al 1999 ); and the cell E m is hyperpolarized in the mouse and other species (Arnoult et al 1999 ;Demarco et al 2003 ;Munoz-Garay et al 2001 ;Zeng et al 1995 ).…”
Section: Capacitationmentioning
confidence: 99%
“…Indeed, hyperpolarization is important in mouse, bovine, and equine sperm capacitation (Arnoult et al 1996 ;Arnoult et al 1999 ;De La Vega-Beltran et al 2012 ;Demarco et al 2003 ;McPartlin et al 2011 ;Munoz-Garay et al 2001 ;Zeng et al 1995 ), although it has not been demonstrated in human sperm. The sperm resting E m is relatively depolarized in most mammalian sperm (between −30 and −40 mV) (De La Vega-Beltran et al 2012 ;Demarco et al 2003 ;Espinosa and Darszon 1995 ;Hernandez-Gonzalez et al 2006 ;McPartlin et al 2011 ;MunozGaray et al 2001 ;Santi et al 2010 ;Zeng et al 1995 ).…”
Section: Membrane Potential Changes During Sperm Capacitationmentioning
confidence: 99%